Chemical composition and antimicrobial activity of different root extracts of Hermannia geniculata against human pathogens of medical importance - Mojau, Pheello Jeremia (University of the Free State (Qwaqwa Campus), 2015)
Hermannia geniculata has been used widely as traditional medicine for treatment agai nst infectious human pathogens. The aim of the study was to determine the antibacterial and anti fungal activities of H. geniculata root extracts and their fractio ns against 16 microbial strains. The dried plant materials were extracted separately in 150 ml of methanol, acetone, ethanol, water and 150 ml (50/50) of hydro-ethanol. Acetone extract inhibited the growth of microorganisms with minimum inhibitory concentration (MIC) values of 1.56 mg/ml against all the tested strains except for Salmonella typhimurium and Candida rugosa at the concentration of 6.25 mg/ml. The ethanol, hydro-ethanol and methanol extracts inhibited bacterial growth with MIC values ranging from3. l 3 mg/ml to 12.50 mg/ml, while water extract had MIC of 12.50 mg/ml against all tested bacterial and fungal strains. Acetone extract had maximum bactericidal concentration (MBC) values ranging from 1.56 to 3.13 mg/ml against most microorganisms. Butanol fraction of acetone extract had MIC of 0.78 mg/ml against Staphylococcus aureus (OK.2b) and Staphylococcus a11re11s (ATCC 6538), whilst the ethyl acetate had the lowest MBC of 1.56 mg/ ml against S. aureus (OK.lb), S. aureus (ATCC 6538), and Streptococcus .faecalis. The extracts and their respective fractions displayed similar inhibitory properties which are indica tions that either the crude extract or their fractions could be used to manage infections assoc iated with bac teria and fungi.
Dissertation (M.Sc. Botany (Plant Sciences))--University of the Free State (Qwaqwa Campus), 2015
Keywords: Medicinal plants; Traditional medicine; Anti-infective agents